NILAI – NILAI KEARIFAN LOKAL GONG WANING PADA MASYARAKAT ETNIS SIKKA KROWE SEBAGAI SUMBER PENDIDIKAN KARAKTER - Gustav Nuwa (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2020)
The purpose of this study was to determine the values ​​contained in gong waning and efforts to maintain the values ​​of local wisdom in the sikka krowe community as a source of character education. The method used in this research is a qualitative descriptive method that is analyzing descriptive data by describing and describing something that exists. This research uses data collection procedures: Observation, Interview, and documentation. , Value of Gratitude, Value of Mutual Respect, and Harmonious Value. There are also efforts to maintain the values ​​of local wisdom in the Sikka krowe community as a source of character education such as: Participation Efforts, Educational Efforts, Togetherness, and Instilling Love to Local Wisdom in the Community ( Especially Sikka krowe Young Generation). By understanding the various values ​​contained in gong waning, the Sikka krowe community is asked to preserve the traditions of the ancestors who are objects of cultural advancement to avoid extinction.